2013
DOI: 10.1016/j.optlastec.2012.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Laser heating induced plastic deformation in a pre-elastic-stretched titanium alloy strip

Abstract: a b s t r a c tExperiment was carried out to reveal the plastic deformation of pre-elastic-stretched titanium alloy strip partially subjected to localized heating via Laser beam irradiation. The temperature profile in the strip under Laser beam irradiation was computed with finite element method. The strain redistribution and localized plastic deformation were analyzed by a one-dimensional model. The results indicate that both the pre-strain level and the ratio of the length of heated range to the total effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The related slope a Q = 2.904 obtained in calculations (7) differs from a BE by 0.5%. The free term b Q = 0.004 m −1 is small and close to the value zero resulting from the analytical dependence for pure bending (10). Laser heating has increased the slope of curvature characteristics by the value k = a L /a Q = 3.56.…”
Section: Hybrid Laser-mechanical Bendingsupporting
confidence: 52%
See 1 more Smart Citation
“…The related slope a Q = 2.904 obtained in calculations (7) differs from a BE by 0.5%. The free term b Q = 0.004 m −1 is small and close to the value zero resulting from the analytical dependence for pure bending (10). Laser heating has increased the slope of curvature characteristics by the value k = a L /a Q = 3.56.…”
Section: Hybrid Laser-mechanical Bendingsupporting
confidence: 52%
“…Such reduction of the involved forces is particularly beneficial when bending thick plates or hard materials. Wu et al [10] analyzed plastic deformation of pre-tensioned strips made of a titanium alloy and heated by the laser beam. The study revealed a large concentration of strain in the heated region.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that the scribable condition could be estimated from the maximum surface tensile stress in the cooling area and the maximum surface temperature. Laser heating induced plastic deformation in a pre-elastic-stretched titanium alloy strip was examined by Wu et al [9]. They showed that both the pre-strain level and the ratio of the length of heated range to the total effective length of the strip influenced considerably the final plastic strain.…”
Section: Introductionmentioning
confidence: 99%